Pendampingan Digitalisasi Madrasah Berbasis Moderasi Beragama dalam Penguatan Mutu Pendidikan Islam di Madrasah Tsanawiyah Ummul Quro Putri Pamekasan - Abdul Hobir; Kurratul Aini; Supandi (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program focused on strengthening madrasah digitalization based on religious moderation to improve the quality of Islamic education at MTs Ummul Quro Putri Plakpak Pegantenan Pamekasan. The program aimed to enhance teachers’ digital literacy, improve digital documentation and communication practices, and integrate religious moderation values into educational technology use. This service employed an Asset-Based Community Development (ABCD) approach through five stages: asset mapping, collective visioning, program design, priority action planning, and participatory implementation. The activities included socialization, digital literacy training, mentoring in digital learning media, strengthening Islamic digital ethics, and organizing digital documentation practices. The results showed increased teacher awareness and skills in using digital media, improved documentation practices, stronger student awareness of ethical digital behavior, and the formation of a small madrasah digitalization team. The program concludes that value-based digitalization can strengthen Islamic education quality when supported by local assets, participatory engagement, and religious moderation principles.